Del Reino al Pueblo. Del himno al anuncio (Teología, 2020)
This paper addresses three issues of permanent actuality: the languages of theology, the links between the Kingdom of God, the Church and the peoples, and the communication of the Gospel. It examines the issues in theological and pastoral dialogue with the recent doctoral thesis of Argentina’s biblical scholar Jorge Blunda, whose work explores the proclamation of God’s reign and its performative function to form the postexilic Israel in the Deutero-Isaiah and Psalms 96 and 98. The author traces a profile of the author and summarizes the core of his contribution. Regarding the form of the text he notes the actuality of prophetic language and the liturgical hymn in theological language. In relation to the essence it indicates the theology of the presence of the king Yhwh and his kingdom in the People of God as a sign of salvation for the people. The article re-reads the strategy to communicate the Good News and to renew the community of faith and contribute to renew the life of our people in the bicentennial celebration of our independence. The article can be situated in the field of the history of theology in Argentina and in the dialogue between biblical scholars and systematic theologians.
Keywords: Kingdom of God; People of God; Peoples; Post exilic Psalms; Language; Prophesy; Ecclesiology; Liturgy; Latin America; Aparecida